Negotiating and contesting 'success': discourses of aspiration in a UK secondary school. Issue 3 (3rd May 2016) - Spohrer, Konstanze
Abstract : The need to 'raise aspirations' among young people from socio-economically disadvantaged backgrounds has been prominent in UK policy debates over the last decade. This paper examines how this discourse is negotiated and contested by teachers and pupils in a Scottish secondary school. Interviews, group discussions and observations were analysed by drawing on Foucauldian discourse analysis. The analysis exposes contradictions and silences inherent in dominant discourses of aspiration, most notably the tension between the promise and the impossibility of 'success' for all. It is argued that attempts to reconcile this tension by calling on young people to maximise individual 'potential' through attitude change silence the social construction of 'success' and 'failure'. The paper concludes with suggesting ways in which schools could embrace the contradictions underpinning dominant 'raising aspiration' discourses and adopt a more critical-sociological approach in working with young people.